Taking Heart: Cardiac Symptoms and Nightmares Differentiate Nightmare Proneness and Psychological Distress among Young Adults - Kelly, William E. (Sleep Science, 2023)
Introduction Nightmare proneness, a trait-like disposition to experience frequent nightmares, has been strongly related to psychological distress. The aim of the present study was to examine if cardiac symptoms and hypothetically-related variables, nightmares, and perceived physical health could be used to differentiate nightmare proneness and psychological distress.Materials and Methods In the present cross-sectional study, 254 young adults completed measures of nightmare proneness, psychological distress, cardiac symptoms, nonspecific and posttraumatic nightmares, nightmare distress, health behaviors, perceptions of physical health, perceived stress, Type-D personality, sleep fragmentation, and dream recall.Results After controlling for psychological distress, nightmare proneness remained significantly correlated with nightmares, nightmare distress, cardiac symptoms, sleep fragmentation, physical health, perceived stress, and Type-D personality. After controlling for nightmare proneness, distress remained correlated with perceived stress and Type-D personality. Regression analyses indicated that after accounting for all variables, nightmare distress, physical health, and nightmare proneness predicted cardiac symptoms. Posttraumatic nightmares, sleep fragmentation, distress, perceived stress, Type-D personality, and chest pain predicted nightmare proneness.Conclusion Nightmare proneness and psychological distress can be considered separate constructs. The findings were consistent with those of previous research and supported the theoretical propositions that nightmare proneness includes hyperarousal, vulnerability to stressors, and concretization, a mental process in which vague internal states are made more concrete.
Keywords: nightmare proneness; psychological distress; nightmares; chest pain; sleep fragmentation